Livogrit Prevents Methionine-Cystine Deficiency Induced Nonalcoholic Steatohepatitis by Modulation of Steatosis and Oxidative Stress in Human Hepatocyte-Derived Spheroid and in Primary Rat Hepatocytes. Issue 4 (1st April 2022) - Balkrishna, Acharya; Gohel, Vivek; Kumari, Priya; Manik, Moumita; Bhattacharya, Kunal; Dev, Rishabh; Varshney, Anurag
ABSTRACT: The prevalence of nonalcoholic steatohepatitis (NASH), characterized by fatty liver, oxidative injury, and inflammation, has considerably increased in the recent years. Due to the complexity of NASH pathogenesis, compounds which can target different mechanisms and stages of NASH development are required. A robust screening model with translational capability is also required to develop therapies targeting NASH. In this study, we used HepG2 spheroids and rat primary hepatocytes to evaluate the potency of Livogrit, a tri-herbal Ayurvedic prescription medicine, as a hepatoprotective agent. NASH was developed in the cells via methionine and cystine-deficient cell culture media. Livogrit at concentration of 30 µg/mL was able to prevent NASH development by decreasing lipid accumulation, ROS production, AST release, NFκB activation and increasing lipolysis, GSH (reduced glutathione), and mitochondrial membrane potential. This study suggests that Livogrit might reduce the lipotoxicity-mediated ROS generation and subsequent production of inflammatory mediators as evident from the increased gene expression of FXR, FGF21, CHOP, CXCL5, and their normalization due to Livogrit treatment. Taken together, Livogrit showed the potential as a multimodal therapeutic formulation capable of attenuating the development of NASH. Our study highlights the potential of Livogrit as a hepatoprotective agent with translational possibilities. Graphical abstract: uf0001